2021
DOI: 10.3390/nano11071865
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Novel Perspectives on Colloids, Hydrogels, and Aerogels Based on Coordination Bonds with Biological Interest Ligands

Abstract: This perspective article shows new advances in the synthesis of colloids, gels, and aerogels generated by combining metal ions and ligands of biological interest, such as nucleobases, nucleotides, peptides, or amino acids, among other derivatives. The characteristic dynamism of coordination bonds between metal center and biocompatible-type ligands, together with molecular recognition capability of these ligands, are crucial to form colloids and gels. These supramolecular structures are generated by forming wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…[54][55][56] Besides carboxylates, several organic ligands are used to assemble MOGs, including pyridines [59][60][61][62][63] and ligands of biological interest. 45 MOGs are built from various metal ions, including transition metal ions, 64 lanthanide ions, [65][66][67][68] and main group metal ions. [69][70][71] The diverse building blocks (metal ions and organic linkers) allow the adjustable chemical structures of MOGs.…”
Section: Metal-organic Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[54][55][56] Besides carboxylates, several organic ligands are used to assemble MOGs, including pyridines [59][60][61][62][63] and ligands of biological interest. 45 MOGs are built from various metal ions, including transition metal ions, 64 lanthanide ions, [65][66][67][68] and main group metal ions. [69][70][71] The diverse building blocks (metal ions and organic linkers) allow the adjustable chemical structures of MOGs.…”
Section: Metal-organic Gelsmentioning
confidence: 99%
“…Although there are some recent review articles in the eld of MOGs, 16,[42][43][44][45][46] a review that comprehensively focuses on the electrochemical applications of MOGs is not available. In this review, we survey the up-to-date research development of MOGs and their applications in the electrochemical elds to promote future breakthroughs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Peptide-based hydrogels are biocompatible soft materials formed by water-swollen networks, and have many applications, from the formulation of membranes to the optimization of tools for delivery of drugs and/or diagnostic agents. [10][11][12]16] However, its structural-morphological and hence functional properties are deeply affected by the amino acid composition of its primary sequence. [16,17] It has already been reported that Fmoc-diphenylalanine (Fmoc-FF) can form hydrogels with selfassembling properties under physiological condition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they should have a high resistance to cracking. The mechanical behavior of these soft materials is currently an important research area and several groups [6][7][8][9][10] have proposed strategies to improve their mechanical properties; for example, reducing heterogeneities in the network in order to reduce nucleating centers for cracks or enhancing the energy dissipation during crack propagation 11,12 . Most hydrogels are chemical hydrogels as they are formed through covalent bonding which implies sophisticated chemistry.…”
Section: Introductionmentioning
confidence: 99%